Micro and macroeconomic determinants of net asset value of Islamic equity unit trust funds : a case study of Malaysia - Othman, Anwar Hasan Abdullah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
Over the past two decades, the Islamic unit trust industry in Malaysia has experienced rapid growth and continues to grow at a fast pace. This high growth highlights the uniqueness of the Islamic unit trust investment which diversifies Sharī'ah compliant asset investments and provides several advantages. Even though the unit trust industry has witnessed high growth in portfolio size, performances, and regulations, various aspects of the industry remain poorly understood due to a general lack of information on the funds' unit price behaviours and mechanisms. Forecasting the price movements in the equity unit trust industry has been a major challenge for various investors, management funds, brokers, and policy makers. This research investigates the effects of microeconomic and macroeconomic variables and the 2007-2008 Global Financial Crisis on the NAV of the Islamic equity unit trust funds. This research utilised the Autoregressive Distributed Lag (ARDL) model and the Vector Autoregression (VAR) model to analyse this relationship over the January 2006 to December 2012 period using monthly data. The results showed a significant long-run equilibrium relationship between the Fund Dividends, Fund Historical Performance, Fund Size, Hedge Funds, Industrial Production Index, Money Supply (M3), Foreign Exchange Rate, Crude Oil Price, Corruption Index, and the NAV of the Islamic equity unit trust funds in the Malaysian capital market. In addition, the causality tests results showed that the Industrial Production Index, National Political Election, and 2007/2008 Global Financial Crisis have significant unidirectional causal effects on the NAV of Islamic equity unit trust funds, while Crude Oil Price has bidirectional causal effect with the NAV of the Islamic equity unit trust funds. The findings of this research will assist investors, fund managers, industry players, and policy makers to estimate and predict the future trend direction of the NAV of Islamic equity unit funds and accordingly make sufficient investment decisions. Key words: Net Asset Value, Islamic Unit Trust, Micro and Macroeconomic Variables, Malaysia